QIRĀʾĀT SYĀDZDZAH DALAM WACANA TAFSIR AL-QUR’AN KLASIK: Studi Kontekstual Atas Kitab Al-Jâmi’ Li Ahkâm Al-Qur’ân - Effendi, Sofian (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
This study critically examines the existence and role of Qirâ’ât Syādzdzah in the classical tafsīr work Al-Jāmiʿ li Aḥkām al-Qurʾān by al-Qurṭubī, as well as its implications for the construction of Qur’anic interpretation. The primary focus of this research lies in exploring how these non-mutawātir readings are treated by classical exegetes in determining legal meanings and normative values derived from the sacred text. Employing a qualitative-descriptive approach through library research, this study analyzes selected verses within al-Qurṭubī’s tafsīr that reference and consider Qirāʾāt Syādzdzah. The findings reveal that the presence of these readings in al-Qurṭubī’s commentary not only showcases variant recitations but also plays a pivotal role in expanding interpretative horizons and enriching the dynamics of tafsīr. The study concludes that Qirâ’ât Syādzdzah possess not only philological and historical significance, but also serve as hermeneutical instruments in the exegetical process of the Qur’an, particularly within the framework of classical tafsīr scholarship.